2016
DOI: 10.1038/srep33238
|View full text |Cite
|
Sign up to set email alerts
|

Study of the effect of excited state concentration on photodegradation of the p3ht polymer

Abstract: We have studied photoinduced reduction of absorption and emission in p3ht, a semiconducting polymer, and found that the rate of photodegradation (destruction of the constituent thiophene rings) does not correlate with the luminescence intensity and, correspondingly, does not depend on the excited state concentration. This conclusion rules out Purcell enhancement of radiative decay rate as a possible explanation of the recently discovered reduction of the p3ht photodegradation rate in the vicinity of metallic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Interestingly, the order of the latter ratios correlated with the order of dielectric permittivities in the metals studied, inset of Figure . (In a separate study, it has been shown that the rate of photodegradation of P3HT does not correlate with the substrate-specific excited state concentration and spontaneous emission of thiophene rings. )…”
Section: Experimental Demonstrationsmentioning
confidence: 94%
See 1 more Smart Citation
“…Interestingly, the order of the latter ratios correlated with the order of dielectric permittivities in the metals studied, inset of Figure . (In a separate study, it has been shown that the rate of photodegradation of P3HT does not correlate with the substrate-specific excited state concentration and spontaneous emission of thiophene rings. )…”
Section: Experimental Demonstrationsmentioning
confidence: 94%
“…Interestingly, the order of the latter ratios correlated with the order of dielectric permittivities in the metals studied, 24 inset of Figure 18. (In a separate study, 115 it has been shown that the rate of photodegradation of P3HT does not correlate with the substrate-specific excited state concentration and spontaneous emission of thiophene rings.) Thus, it has been unambiguously proven 24 that the rates of chemical reactions can be controlled not only by local dielectric permittivities, but also by nonlocal dielectric environments.…”
Section: Acs Photonicsmentioning
confidence: 95%
“…The light-induced applications of OSCs described above exploit the relaxation processes following photoexcitation, such as photoluminescence, heat generation due to the internal conversion of the excited state, or electron transfer to a nearby molecule, leading to the generation of radical chemical species. The relaxation processes are coupled and in dynamic competition, which can lead to non-linear responses to light exposure ( Peters et al, 2016 ). On the biological side, effects of undesired relaxation pathways must be carefully considered to pair OSCs effectively and reliably to their intended applications.…”
Section: Introductionmentioning
confidence: 99%
“…In these regards, an interesting route would be the use of plasmonic materials or optical resonators that are spectrally tuned with P3HT absorption, so that their optical coupling would lead to an enhancement of the local electromagnetic field experienced by the polymer. Recently, metallic surfaces have been used to control the rate of P3HT photodegradation, , while the use of metamaterials to achieve field enhancement has been proposed for improving the power conversion efficiency in organic solar cells. , Some recent works investigated the optical response of such devices in biological processes. However, to the best of our knowledge, such an approach has never been employed systematically to modulate the photodriven effects at the abiotic/biotic interface.…”
Section: Introductionmentioning
confidence: 99%